Purple Potato Extract Promotes Intestinal Epithelial Differentiation and Barrier Function by Activating AMP‐Activated Protein Kinase. Issue 4 (25th January 2018) - Sun, Xiaofei; Du, Min; Navarre, Duroy A.; Zhu, Mei‐Jun
Abstract : Scope: Perturbation of gut epithelial barrier function induces inflammation and other health problems that originate from the gut. Purple potato contains a high content of beneficial polyphenolic compounds. The objective of this study is to evaluate the effect of purple potato extract (PPE) on intestinal differentiation and barrier function, and explore its underlying mechanism using Caco‐2 cells and ex vivo cultured gut tissues. Methods and results: PPE increases transepithelial electrical resistance and decreases FITC‐dextran paracellular flux in Caco‐2 cells, which are associated with strengthened intestinal epithelial differentiation in both Caco‐2 cells and ex vivo guts. Furthermore, PPE treatment enhances AMP‐activated protein kinase (AMPK) activity, concomitant with the increased expression of CDX2, a key transcriptional factor regulating intestinal epithelial differentiation. Knocking out AMPK using CRISPR/Cas9 system abolishes the positive effects of PPE on intestinal epithelial differentiation and barrier function, in junction with the reduced expression of CDX2. Conclusion: PPE improves gut epithelial differentiation and barrier function via activating AMPK, indicating that PPE, as well as associated purple potato consumption, could be used as a supportive dietary therapeutic strategy for improving gut epithelial health. Abstract : Purple potato extract (PPE) increases transepithelial electrical resistance (TEER) and decreases paracellular permeability via activating AMP‐activated protein kinase (AMPK) in intestinal epithelial cells. Activated AMPK promoted the expression of CDX2, regulating epithelial differentiation, such as the tight junction in paracellular space. PPE improved gut barrier function, indicating that PPE as well as associated purple potato consumption could be used as a supportive dietary therapeutic strategy for improving gut epithelial health.